The impacts of copper, iron and manganese metal ions on the EPR assessment of beer oxidative stability. - Jenkins, David; James, Sue; Dehrmann, Frieda; Smart, Katherine; Cook, David (American Society of Brewing Chemists, 2018)
Beer flavour stability is a key quality parameter as brewers seek to maintain the quality of their product throughout the supply chain. The electron paramagnetic resonance (EPR) oxidative stability assay is one method that brewers are utilising to optimise their process with regards to flavour stability without the time requirements of stored aging and sensory testing of beer. There are still gaps in knowledge relating to the EPR measurement and the factors within the assay that affect the measured results. This investigation aimed to understand the influence that transition metal ions have on the measurement in four different beers (three lagers and one stout). The detrimental impact of copper and iron on the lag time (an indication of when staling may begin) of trial beers is demonstrated, whilst the influence of manganese is shown to differ between beers. The T450 value (an indication of how much staling may occur in a particular beer) is shown to increase with iron and manganese addition in most beers. However, copper reduces the T450 or maximum spin adduct concentration achieved and the potential reasons for this are discussed. Crucially for brewers it has been shown that as little as 10 ppb transition metal ion addition can make detectable difference to the measured oxidative stability.